القيم الجمالية للتصميم الجرافيكي البيئي الرقمي - عناد، دينا محمد (جامعة اليرموك - عمادة البحث العلمي, 2017)
جاءت هذه الدراسة لتوضح الموضوع بأربعة فصول، تضمن مشكلة البحث والحاجة إليه، وقد كانت المشكلة تتمثل بالسؤال الآتي (ماهي القيم الجمالية للتصميم الجرافيكي البيئي الرقمي (؟ أما هدف الدراسة فكان تقديم دراسة علمية للتعرف على القيم الجمالية للتصميم الجرافيكي البيئي الرقمي، وتقديم مقترح إعادة تصميم ملصق يتضمن قيما جمالية بيئية. كما ضم أهمية البحث وحدود البحث فضلا عن تحديد المصطلحات. والإطار النظري، مكون من ثلاثة مباحث ركز المبحث الأول على (مفهوم القيم الجمالية) والمبحث الثاني على (التصميم الرقمي وعلاقته بالبيئة والإنسان) وتضمن المبحث الثالث (جماليات التصميم الجرافيكي البيئي الرقمي. وفي تحليل العينات اتبعت الباحثة المنهج الوصفي وطريقة تحليل المحتوى، ولغرض تحليل العينة تم الاعتماد على ما تمخض عنه الإطار النظري من أدبيات متعلقة بموضوع البحث لتسهم في تحقيق هدف البحث. وبني التحليل على أساسها. ثم أتبعت بأهم والاستنتاجات.
This paper is intended to treat subject in four sections chapters. The first section deals with the problem of research and its need. The problem is identified as follows: (What are the aesthetic values of digital environmental graphic design)? The objective of the study was to identify the aesthetic values of digital environmental graphic design and to propose a redesign of a poster that includes environmental aesthetic values. The paper highlishts the importance of the study andprorides and its limit definition of terms. The second section focuses on the digital design and its relation to the environment and man, and the third deals with aesthetics of digital graphic design. In The third section of the research procedures were determined. The researcher followed the descriptive approach and the method of content analysis. The analysis of the sample was based on the review oflitreture on the theoretical framework of research subject. The fourth section of this study included the most important findings and conclusions. The researcher included the recommendations and presented a proposal to redesign a poster containing environmental aesthetic values.
Keywords: التصميم الجرافيكي -- التصميم الرقمي -- القيم الجمالية -- التصميم البيئي